Effect of Addition Different Nano-Particle Materials on Some Mechanical and Physical Properties of Polymethyl methacrylate Resin - In Vitro Study - Osama S. Abdelhamid,; Ahmed El-Okl,; Othman S. Alsulaimani,; Abdulrahman J. Alhaddad,; Samar H. Abuzinadah,; Osamah A. Alsulimani,; Amany A. ElHadary,; Emad Boriqaa, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective:This study aimsto evaluate a heat-cured polymethyl methacrylate resin material modified with different concentrations of silver (Ag) and zirconium oxide nanoparticles (Nps) regarding impact strength, flexure strength, and water sorption. Material and Methods:For this study, 75 specimens were processed according to the specifications of each test (Impact strength, flexural strength, and water sorption). Specimens were divided into five groups according to the type and concentrations of Nps materials added to PMMA powder: Group A: control group only conventional heat cured PMMA resin, group B: PMMA reinforced with 0.5% Ag oxide Nps, group C: PMMA reinforced with 1% Ag oxide Nps, group D: PMMA reinforced with 0.5% zirconium oxide Nps, and group E: PMMA reinforced with 1% zirconium oxide Nps. Results:Regarding the impact strength and water sorption, there was an insignificant increase for all modified groups compared with the control group, While theflexural strength value decreased significantly after the addition of nanoparticle materials (P<0.05). Conclusions: Based on the findings of this study, we can conclude that the addition of different concentrations of silver and zirconium Oxide nanoparticles to the PMMA denture base material led to a slight increase in the impact Strength and water sorptionwith decreasing the flexure strength.